Antibodies to meningococcal class 1 outer membrane proteins in South African complement-deficient and complement-sufficient subjects. - Orren, A (1992)
Inhibition assays were used to investigate human serum antibodies to the meningococcal class 1 outer membrane proteins. We adapted the whole-cell enzyme-linked immunosorbent assay technique to determine the ability of sera to inhibit the binding of murine subtyping monoclonal antibodies. Serum samples from 33 South African subjects with a deficiency in the sixth component of complement as well as serum samples from various groups of complement-sufficient subjects were investigated. Subjects were subdivided according to whether they were (i) convalescent from Neisseria meningitidis infections, (ii) nonconvalescent, or (iii) controls. Preliminary subtyping investigations had shown that P1.2 was present on 36% of meningococcal clinical isolates from Cape Province, South Africa. Assays with the anti-P1.2 antibodies showed the presence of high antibody levels in many deficient sera and moderately elevated levels in some sera from the complement-sufficient convalescent patients. P1.2, P1.4, P1.15, and P1.16 are epitopes situated on loop 4 of the class 1 outer membrane proteins, whereas P1.7 is on loop 1. Inhibition assays showed that human sera that inhibited binding by P1.2 monoclonal antibodies tended to inhibit the other monoclonal antibodies directed to loop 4 epitopes. This suggests that the epitopes recognized by the human antibodies are not exactly the same as the epitopes recognized by the murine monoclonal antibodies and raises the possibility of the importance of other epitopes.